Implementation of Guidance and Counseling Services at SMPN 2 Teluk Jambe Timur Karawang - Helma Noviyani; Mimin Maryati (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
Implementation of guidance and counseling service activities in schools begins with needs assessment, program planning (RPL), activity implementation, evaluation, analysis, activity reports, and follow-up on service results. The problems that are often experienced by students are about their own personality and family background so that they have an impact on the teaching and learning process at school and affect their peers, with diverse family backgrounds, BK teachers are very productive in handling students at school to call their parents to follow up, it is very necessary for the role of parents who must always pay attention to the development of children from an early age so that it does not have a negative impact on the learning process. Especially with the current complex situation, parents play an important role in guiding their children to continue learning even if only from home by only relying on student gadgets and parents are more diligent in carrying out education in order to become smart children and have good character. With this developmental task, guidance and counseling services which are an integral part of education must be able to provide color in realizing students can refine, internalize and integrate their developmental tasks optimally so that the orientation of guidance and counseling is oriented towards individual development is usually applied in accordance with the expectations and goals of the individual. education.